Entrepreneurial intention and the three stages of entrepreneurial action: a process approach - Dlamini, Mzwakhe; Botha, Melodi (Frontiers in Psychology, 2023)
The relationship between entrepreneurial intention (EI) and entrepreneurial action (EA) is a popular topic in entrepreneurship research, owing to the contribution of these constructs in the process leading to the entrepreneurial activity taking place. There are still countries that are recording high entrepreneurial intention levels in comparison to their corresponding entrepreneurial action levels that are low. This is a global concern to which South Africa (SA) is also not immune. Most of the research tests the relationship between two single constructs: EI and EA. Our study follows a process approach and investigates the effect of this relationship between EI and the three stages of EA. A quantitative method was employed and a survey utilized whereby data was collected among 597 entrepreneurs in South Africa. The data was analyzed through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The EI construct is supported through the Theory of Planned Behavior, in conjunction with the Motivation Opportunity Ability theory. The Discovery Theory, together with the Creative Theory, supports each of the stages of EA, namely: entrepreneurial opportunity discovery (EODI); entrepreneurial opportunity evaluation (EOEV); and entrepreneurial opportunity exploitation (EOEX). Previous research regarding the relationship between EI and EA measured this relationship from a binary point of view. This study contributes to the entrepreneurship field by employing the process approach to determine the impact of EI on the stages of EA. This study reveals that EI is statistically significant in all three stages of EA. However, the strength of this relationship is found to be strong between EI and the EODI and EOEV stages and moderate between EI and the EOEX stage. Therefore, this study reveals that effective training interventions and development are necessary between EI and the EOEX stage of EA.